Effect of Liquidity, Productivity and Firm Size on Bond Ranking - Suharmadi SUHARMADI; Suripto SURIPTO (Indonesia Strategic Sustainability, 2021)
The purpose of this research was to analyze the effect of liquidity, productivity and firm size on bond ratings on non financial companies in ranked PT PEFINDO and listed on the Indonesia Stock Exchange in the period 2016-2019. The sampling method used was purposive sampling method in order to obtain 31 non financial companies with a total research of 93 samples. The data analysis technique used in this research is multiple linear regression analysis with IBM SPSS version 25 software. The results of this research indicate that the liquidity variable which is proxied by current ratio has no significant effect on bond ratings. While the productivity variable which is proxied by total asset turnover and firm size which is proxied by natural log total assets has a significant positive effect on bond ratings.